DESIGN OF PURSE SEINER IN THE SIBOLGA ARCIPELAGO FISHING PORT PROVINCE NORTH SUMATERA - Lina, Renta; Nasution, Polaris; Zain, Jonny (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The Successfull of fishing catch effort very be effected by the fisheries resources available, fishing fleet and fishing gear used a accordance waters condition and species of fish in the waters. For optimally utilize the resources potential of the research needed determination carryng capacity, an adequate number and size of the fishing ship needed. Waters of the west Sumatera coast has potential of fishing is utilized along 23% of the available potential, which is dominated catches small pelagic. So, have needed this research to develop the purse seine fisheries business in particular. The method used in this research is a survey method of data collection and direct observation to the field, then the data is processed using regression analysis, comperative ship, designing ship with the NSP method. For the next 25 years, along with the effectiveness lifespan of the vessel, need an additional 21 purse seiner, 88 gross tonnage, 52,117 net tonnage, 21 meters LPP, 6,924 meters breath, 2,18 meters high and 1,86 meters maximum draft.Keyword : Design, Fishing Ship, Purse Seine, PPN Sibolga and Small Pelagic.